SOFTWARE REQUIREMENT DALAM MEMBANGUN SISTEM INFORMASI PELAYANAN PUBLIK - Nugraha, Deny Wiria (MEKTEK, 2011)
This study examines in depth about the software requirements to build a public information service system. Inprinciple, this research aims is to develop a plan needs public information service system that can assist andaccelerate the process of public service and reduce errors so that the information will result in services that can beaccounted for. This research is expected to contribute to the academic world is to add insight and knowledgeabout software engineering and information systems of public service.Software public information service system is designed with an interface easy to understand Indonesianlanguage, web application, multiple-login, can be integrated with computer networks, and built with PHPscript programming language, database used is MySQL, as well as web server used is AppServ 2.2